Aqua{6,6′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethylidyne)]diphenolato}methanolmanganese(III)) perchlorate hemihydrate - Gervas Assey (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, [Mn(C18H18N2O4)(CH3OH)(H2O)]ClO4·0.5H2O, contains two complex cations and two perchlorate anions, one of which is disordered over two positions in a 0.767 (8):0.233 (8) ratio. The MnIII atoms are in distorted octahedral environments. In addition to the equatorial tetradentate salicylaldimine ligand, each Mn is axially coordinated by both a methanol and a water molecule. The complex is a dimer held together by multiple strong and weak hydrogen-bonding interactions between the coordinated water molecule on one monomer with all the phenolic and methoxy O atoms on the other monomer. In addition, the two perchlorate anions are linked by hydrogen bonds to the two methanol molecules coordinated to each Mn center. The Mn—O phenolic bond distances range from 1.868 (2) to 1.882 (2) Å while the Mn—N distances range from 1.978 (2) to 1.981 (2) Å. Mn—O distances for the axial water and methanol ligands are longer at 2.226 (2)/2.257 (2) and 2.313 (2)/2.324 (2) Å, reflecting the usual Jahn–Teller distortion as found in MnIII complexes.